The myth of cognitive agency: subpersonal thinking as a cyclically recurring loss of mental autonomy - Metzinger, Thomas K. (Frontiers in Psychology, 2013)
This metatheoretical paper investigates mind wandering from the perspective of philosophy of mind. It has two central claims. The first is that on a conceptual level, mind wandering can be fruitfully described as a specific form of mental autonomy loss. The second is that most of what we call “conscious thought” is better analysed as a subpersonal process that more often than not lacks crucial properties traditionally taken to be the hallmark of personal-level cognition, such as mental agency, explicit, consciously experienced goal-directedness, or availability for veto control. I claim that for roughly two thirds of our life-time we do not possess mental autonomy (M-autonomy) in this sense. Empirical data from research on mind wandering and nocturnal dreaming clearly show that phenomenally represented cognitive processing is mostly an automatic, non-agentive process and that personal-level cognition is an exception rather than the rule. This raises an interesting new version of the mind-body problem: How is subpersonal cognition causally related to personal-level thought? More fine-grained phenomenological descriptions for what we called “conscious thought” in the past are needed, as well as a functional decomposition of umbrella terms like “mind wandering” into different target phenomena and a better understanding of the frequent dynamic transitions between spontaneous, task-unrelated thought and meta-awareness.. In an attempt to lay some very first conceptual foundations for the now burgeoning field of research on mind wandering, the third section proposes two new criteria for individuating single episodes of mind-wandering, namely, the “self-representational blink” (SRB) and a sudden shift in the phenomenological “unit of identification” (UI). I close by specifying a list of potentially innovative research goals that could serve to establish a stronger connection between mind wandering research and philosophy of mind.